Genome-wide survey of peptides containing tyrosine sulfation (PSY) gene family and potential PSY specific miRNA revealed their role in plant development and diverse stress conditions in rice (Oryza sativa L.) - Mahipal Singh Kesawat; Swati Manohar; Bhagwat Singh Kherawat; Santosh Kumar; Sangram K. Lenka; Parameswaran C; Jawahar Lal Katara; Seema Tripathy; Hyun Uk Kim; Sang-Min Chung; Manzer H. Siddiqui; Saud Alamri; et al. (Plant Stress, 2024)
Signalling peptides play a vital role in regulating a wide range of aspects, including plant growth, development, and responses to various biotic and abiotic conditions. In recent times, small post-translationally altered peptides have garnered significant attention from plant biologists due to their crucial role as signalling molecules in various biological processes. Until now, the biological function of peptides containing Tyrosine Sulfation (PSY) gene family members has only been elucidated in Arabidopsis. However, their functions in plant developmental processes and their responses to different biotic and abiotic stress conditions remain elusive in other crops. Therefore, in this study, we identified 109 PSY genes in the rice genome for the first time. However, our detailed in silico analysis focused specifically on 7 OsPSY genes of the O. sativa Japonica Group (Nippobare). Phylogenetic analysis of PSY genes from various plant species has classified these genes into eight distinct groups, designated as Group I to VIII. Interestingly, the 7 OsPSY genes identified in rice were found to be distributed across all four groups including I, V, VI and VIII. In addition, closely linked groups of PSY genes showed more similarities in terms of gene structures, conserved motif distributions, and corresponding subcellular locations. Further, the Ka/Ks score analysis revealed that OsPSY genes have undergone significant purifying selection throughout their evolutionary history. Furthermore, multiple CAREs were discovered in the OsPSY promoters, suggesting their potential importance in regulating plant growth, responses to plant hormones, and multifactorial stress conditions. Additionally, the potential miRNAs that specifically targeted to OsPSY genes were identified and also examined their expression kinetics in different tissues and developmental stage. Out of the seven OsPSY genes, six OsPSY genes were found to be targeted by twelve miRNAs. Moreover the expression profile of OsPSY genes showed a differential expression pattern in various tissues and multifactorial stress conditions. Therefore, these findings serve as a valuable reference for further molecular studies aimed at enhancing the yield and stress tolerance of rice. The understanding the functions and regulatory mechanisms of the OsPSY genes can potentially lead to the development of targeted approaches to improve crop performance under various environmental conditions, ultimately contributing to agricultural productivity and global food security.